Consumo de hojas por herbívoros en manglares del estuario del Río Dagua, Costa Pacífica Colombiana - C. Romero, Isabel (2006)
Herbivore leaf consumption of various mangrove species in relation to environmental factors and leaf hardness were studied in the Dagua river estuary, Colombia. Leaf consumption and damage were assessed by measuring the percentage of area attacked by herbivores, distinguishing between consumption and dam-age. The species that suffered the highest consumption, such as Avicennia germinans (Avicenniaceae) and Laguncularia racemosa (Combretaceae), had softer leaves and less herbivore species when compared with Rhizophora spp. (Rhizophoraceae) and Pelliciera rhizophorae (Theaceae). The abundance and diversity of leaf grazing and its variability among mangrove species in the Dagua River estuary, show the importance of the tro-phic dynamics of live vegetable matter,in spite of their relatively low contribution to removing organic matter.